2012
DOI: 10.1093/jxb/err424
|View full text |Cite
|
Sign up to set email alerts
|

A loss-of-function mutation in the nucleoporin AtNUP160 indicates that normal auxin signalling is required for a proper ethylene response in Arabidopsis

Abstract: As part of a continuing effort to elucidate mechanisms that regulate the magnitude of ethylene signalling, an Arabidopsis mutant with an enhanced ethylene response was identified. Subsequent characterization of this loss-of-function mutant revealed severe hypocotyl shortening in the presence of saturating ethylene along with increased expression in leaves of a subset of ethylene-responsive genes. It was subsequently determined by map-based cloning that the mutant (sar1-7) represents a loss-of-function mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…These phytohormones relieve plants from abiotic stresses and improve their survival rates [56,114,115]. There is an array of phytohormones, such as the cytokinins, auxins, gibberellins, ethylene, abscisic acid, and jasmonates, which either promote shoot growth or regulates growth-inhibitory processes in plants such as dormancy, abscission, and senescence, thereby controlling growth activities in plants [116][117][118]. Abscisic acid is vital to the opening and closing of the stomata, especially when plants are stressed.…”
Section: Indole-3-acetic Acid (Iaa) Induced Drought Tolerance In Planmentioning
confidence: 99%
“…These phytohormones relieve plants from abiotic stresses and improve their survival rates [56,114,115]. There is an array of phytohormones, such as the cytokinins, auxins, gibberellins, ethylene, abscisic acid, and jasmonates, which either promote shoot growth or regulates growth-inhibitory processes in plants such as dormancy, abscission, and senescence, thereby controlling growth activities in plants [116][117][118]. Abscisic acid is vital to the opening and closing of the stomata, especially when plants are stressed.…”
Section: Indole-3-acetic Acid (Iaa) Induced Drought Tolerance In Planmentioning
confidence: 99%
“…The sites of action and production of these phytoregulators are generally quite distant from one another (Avanci et al, 2010;Liu et al, 2012). According to the classical view, five major classes of phytohormones are auxins, cytokinins, gibberellins, ethylene and abscisic acid (Jamil et al, 2012;Robles et al, 2012) but there is increasing evidence of other compounds to have shown growth regulating activities in plants. Among these are brassinosteroids, jasmonates, salicylic acid, strigolactones, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Auxins, cytokinins, gibberellins and brassinosteroids promote shoot growth while others including ethylene, abscisic acid and jasmonates control growth activities by regulating growth inhibitory processes in plants such as dormancy, abscission, senescence etc. (Acosta and Farmer, 2010;Dempsey et al, 2011;Costigan et al, 2011;Liu et al, 2012;Robles et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Nup proteins SUPPRESSOR OF AUXIN RESISTANCE 1 (SAR1, Nup160) and 3 (SAR3, Nup96) are required for the nuclear import of auxin (AUX) and (or) indole-3-acetic acid (IAA) proteins that are the repressors of auxin-inducible gene expressions (Parry et al 2006). SAR1 also mediates the ethylene signaling pathway (Robles et al 2012). The karyopherin protein MODIFIER OF SNC1, 6 (MOS6) and the Nup proteins MOS3 (Nup96) and MOS7 (Nup88) are crucial to the nuclear import of the key SA signaling regulator NON-EXPRESSER OF PR GENES 1 (NPR1) (Cheng et al 2009).…”
Section: Introductionmentioning
confidence: 99%